Butterfly Stroke Teaching Aid #1 - Rushall, B. S. (1999)
The collage of sequences from some of the world's best butterflyers (Mary T. Meagher, Denis Pankratov, Susan O'Neill) is presented as teaching aids in Dr. Rushall's Stroke Clinics. Each item is presented to show important features of the stroke that should be adapted to each individual's capabilities.